Peak Metamorphic Conditions of Garnet Amphibolite from Luk Ulo Complex, Central Java, Indonesia: Implications for Medium-Pressure/High-Temperature Metamorphism in the Central Indonesian Accretionary Collision Complex - Setiawan, Nugroho Imam; Osanai, Yasuhito; Nakano, Nobuhiko; Adachi, Tatsuro; Hendratno, Agus; Sasongko, Wahyu; Ansori, Chusni (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.3.225-239Garnet amphibolites, which suggest medium-pressure/high-temperature (MP/HT), are widely recognized in Luk Ulo Complex, Central Java. Their occurrences associated with high-pressure/low-temperature (HP/LT; eclogite, blueschist) metamorphic rocks in the Luk Ulo Complex will provide important constraint on the geodynamic model of Central Indonesian Accretionary Collision Complex (CIACC). This study aimed to estimates P-T metamorphic condition of garnet amphibolite from Luk Ulo Complex by using mineral parageneses, thermodynamic data, and NCKFMASHO pseudosection. Prograde stage assemblages represented by inclusions in the garnet, which are garnet core, zoisite, titanite, apatite, and quartz. Mineral coexistences at the peak P-T condition are garnet rim, magnesio-hornblende, zoisite, titanite, quartz, albite, and phengite. The retrograde stage represented by secondary minerals fill the crack in the garnet and other minerals, which are chlorite and quartz. P-T metamorphic condition of garnet amphibolite can only be interpreted from the peak metamorphic stage. The temperature of the garnet amphibolite is estimated using the garnet-amphibole and garnet-phengite geothermometers. Meanwhile, the pressure condition is estimated from phengite geobarometer. The results were compared to the stability and compositions of the phases in NCKFMASHO pseudosection in order to constrain the peak P-T metamorphic conditions. It is concluded that the peak P-T metamorphic condition for garnet amphibolite is 0.9 - 1.4 GPa and 558 - 606 ÂºC. The estimated peak P-T metamorphic temperature is higher compared to the previously published gradient geothermal of eclogite and tourmaline-eclogite in the Luk Ulo Complex. The MP/HT (amphibolite) and HP/LT (blueschist and eclogite) metamorphic rocks could have similar metamorphic ages if both footwall and hanging wall had initially very high thermal gradients and the rate of subduction was very slow (10 km/Ma or less).